2022
DOI: 10.1002/adfm.202211571
|View full text |Cite
|
Sign up to set email alerts
|

The Golden Touch by Light: A Finely Engineered Luminogen Empowering High Photoactivatable and Photodynamic Efficiency for Cancer Phototheranostics

Abstract: Photoactivatable agent is a powerful tool in biomedicine studies due to highprecision spatiotemporal control of light. However, those previously reported agents generally suffer from short wavelength, fluorescence self-quenching effect, and the lack of photosensitizing property, which severely restrict their practical applications. To address these issues, molecular engineering of 1,4-dihydropyridine derivatives is conducted to obtain an optimized agent, namely TPA-DHPy-Py, which exhibits low oxidation potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…It indicates that formation of MC under irradiation benefits the disaggregation of aromatic J-type aggregates in lignin. [39] Meanwhile, the peak intensity at 580 nm gradually increases and reaches the maximum after 12 min. When the irradiation time further extends to 60 min, the peak intensity have nearly no change, indicating the MC structures in AL-SP 3 have good stability.…”
Section: Anti-fatigue Mechanism Of Al-sp Nmentioning
confidence: 98%
“…It indicates that formation of MC under irradiation benefits the disaggregation of aromatic J-type aggregates in lignin. [39] Meanwhile, the peak intensity at 580 nm gradually increases and reaches the maximum after 12 min. When the irradiation time further extends to 60 min, the peak intensity have nearly no change, indicating the MC structures in AL-SP 3 have good stability.…”
Section: Anti-fatigue Mechanism Of Al-sp Nmentioning
confidence: 98%
“…ROS, such as hydroxyl radicals (•OH) and superoxide anions (•O 2 − ), are recognized as the most useful oxidants in cancer treatment and adjuvants in cooperative chemotherapy, because they can facilitate the oxidative damage of cancer cells and improve the anticancer effect. [20][21][22][23][24][25] Therefore, a special prodrug that does not rely on ROS as a trigger but can respond to ultrasound, directly release chemically toxic drugs and even produce ROS has significant application prospects in tumor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in comparison to the conventional fluorophores, AIEgens show a larger Stokes’ shift, greater luminosity, photobleaching resistance, and biocompatibility, leaving a lot of potential for developing novel anticancer photosensitizers . Indeed, benefiting from the intense ROS generation or heating in situ , AIEgens that target different organelles, such as mitochondria, nuclei, Golgi apparatus, and ER, have been verified with high efficiency in triggering cancer cell death and tumor ablation. Nevertheless, intrinsic drawbacks like collateral thermal injury of PDT and oxygen dependence of PDT still restricted the anticancer application of photosensitizers in vivo . Notably, previous studies have revealed some exciting bioactivities that activate mitochondrial autophagy and lysosomal maturation after the binding of AIEgens to subcellular organelles. , Although such physiological regulation focuses on the antibacterial immunities, these findings still remind us of the enormous potential of AIEgens for oncotherapy based on the further exploitation and utilization of pharmacological activities other than PDT and PTT.…”
Section: Introductionmentioning
confidence: 99%